Features of the child trafficking mechanism - Shomakhova, V. D.; Шомахова, В. Д.; Salmanov, O. V.; Салманов, О. В. (My University, 2024)
Торгівля дітьми є особливою категорією кримінального правопорушення, окремо від злочину, передбаченого статтею 149 Кримінального кодексу України. Слід зазначити, що в кримінальному законодавстві багатьох країн (особливо європейських) злочин торгівля дітьми також відокремлений від злочину торгівлі людьми.

Trafficking in children is a special category of criminal offense, separate from the offense provided for in Article 149 of the Criminal Code of Ukraine. It should be noted that in the criminal legislation of many countries (especially European ones), the offense of trafficking in children is also separated from the offense of human trafficking. Of course, from an official point of view, these offenses represent a very small proportion, but there are still many unregistered cases of child trafficking. The long incubation period of these offenses can be explained by several factors. First, due to their flexible and unformed psyche, children quickly adapt to situations of exploitation and perceive them as the norm, so they rarely resist offenders or seek help from law enforcement agencies or the public. That is, usually children cannot protect themselves due to physical inequality with an adult or a misleading perception of the situation. Secondly, due to the specifics of development, victims often cannot give full and objective evidence about the offender's behavior (preschoolers and young children). Third, the transfer of children for the purpose of exploitation is usually outwardly legal.
Особливості механізму вчинення торгівлі дітьми
Keywords: criminal proceedings; торгівля людьми; торгівля дітьми; протидія торгівлі людьми; Україна; human trafficking; child trafficking; combating human trafficking; Ukraine